Travel Patterns and Visitor Satisfaction Levels for The International Folk and Art Festival Event: Study in Kutai Kartanegara, Indonesia - Said Keliwar; Muhammad Fauzan Noor; Nurul Diyana Binti Md Khairi (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This research aims to identify the characteristics of visitor patterns and levels of satisfaction as well as factors that encourage visitors to visit The International Folk and Art (TIFAF) event held in Kutai Kartanegara, Indonesia. The research also seeks to evaluate the overall satisfaction level of attendees and identify key indicators contributing to visitor experience. This research employs a combination of qualitative and quantitative approaches. The tool used to analyze the research data is IBM SPSS version 22. The study employs frequency analysis to examine the characteristics and perceptions of visitors. Data analysis related to the perceptions of visitors and business actors is conducted using the Level of Respondent Achievement (LRA) method, which includes 16 evaluation indicators. The sampling method used is accidental sampling with 682 respondents. The findings indicate that the majority of TIFAF visitors were male (62%), aged between 17 and 25 years (68%), and predominantly students or university students (60%) with a high school level education (65%) and monthly income below IDR 500,000 (59%). Visitors expressed high levels of satisfaction with the event, reflected by an average perception score of 37.5 and an overall TCR of 85.99%. These results demonstrate a positive reception across all assessed aspects, underscoring the festival’s success in meeting visitor expectations. The findings offer actionable insights for improving future cultural tourism events in the region.